Επίδραση της χρήσης ελαιοπλακούντα στην διατροφή των αιγών Δαμασκού ως προς την ποσότητα και ποιότητα του παραγομένου γάλακτος - Δαμιανού, Κωνσταντίνος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This study examined the use of olive cake silage in the feeding of dairy Damascus goats. For the purposes of the experiment, 72 pure-bred Damascus goats were selected, after weaning their kids (at 49 days), and allocated into three groups balanced for milk yield (mean of 2,81 kg ± 0,5 per day, body weight , the lactation period and number of kids The first group (M) was used as a control with no consumption of olive cake, the second group (A) consumed 0.5 kg (on fresh basis) nd the third group (B) consumed 1 kg of olive cake per goat per day. The experiment lasted six weeks. The total feed for the three groups had the same protein and energy content. The olive cake silage was prepared for 40 days and the feed remained in the silage pit until it was offered to the experimental animals. During the experiment, measurements were made regardign the quantity and quality of milk, the consumption of feed and the body weight of goats. The experimental feed was consumed in total, while there was no difference in the goat body weight of the different groups at the end of the experiment (mean BW 61 kg ± 10). The daily milk production in all groups was descending during the experiment period without statistically significant difference between groups (mean milk yield 2,61 kg ± 0,78, 2,67 kg ± 0,82 and 2,65 kg ± 0, 60 for groups M, A and B, respectively). The percentage of fat in the milk did not differ between the groups (3,12% ± 0,29, 3,14% ± 0,47 and 3,23% ± 0,43 for groups M, A and B, Respectively). On the other hand, the milk protein in groups A and B, which administered the olive cake silage was higher compared to group M from the second week of administration till the end of the experiment (average values for the week 2 to 6were: 3.71% ± 0.21, 3.81% ± 0.18 and 3.83% ± 0.15 for groups M, A and B, respectively, P <0.05). The present experiment has confirmed the possibility of providing this cheap by-product (olive cake) to goats without any adverse effect on the production or quality of goat milk, while an increase in the protein content of milk has been observed, which requires more investigation.
Keywords: Silage olive cake; Damascus goats; Goat’s milk; Fat; Protein; Ενσίρωμα ελαιοπλακούντα; Αίγα Δαμασκού; Αιγινό γάλα; Λιποπεριεκτικότητα; Πρωτεΐνη